EEG and MRI in Identifying Tuberous Sclerosis Lesions for Epilepsy Surgery - J Gordon Millichap (Pediatric Neurology Briefs)
The role of surface EEG and MRI in the identification of epileptogenic tubers for surgical resection in patients with tuberous sclerosis (TSC) was studied at the Cleveland Clinic, OH.